Empathy therapy to raise awareness of verbal bullying hazards - Dini Mai Hesty; Dedy Surya (Institut Agama Islam Negeri Langsa, 2020)
The low awareness of verbal bullying hazard is caused by a low of empathy in individuals. Empathy therapy can be used to develop a sense of empathy, and it can raise awareness about verbal bullying hazard, thereby minimizing the tendency of verbal bullying. This study aims to see the effectiveness of empathy therapy for raised awareness of verbal bullying hazards. This research used a quantitative approach-quasi experimental (one group pretest-posttest design), with a purposive sampling technique, sample by six female participants between ages 17 and 19 in Gampong Paya Bujok Tunong. The instrument used in the research is the tendency scale of verbal bullying. The finding showed that there was a significant empathy therapy decreasing the tendency of verbal bullying.